THE MANAGEMENT COMPONENT OF THE ECONOMIC POTENTIAL OF A REGION - N. Nesterova (Финансы: теория и практика, 2017)
Currently in line with global trends, the development of globalization and growing competition between different territories of the Russian Federation, there is an urgent need to involve and use all sources and resources of the territories in the process of regional economic capacity building for providing a sustainable, balanced social and economic growth of regions. Activating and promotion of local features, resources, initiative and creativity can best be manifested at the regional level and this is especially important for Russia given limited possibilities of the centralized management. The management component of the economic potential is taking on special significance as it directly interacts with other components of the economic potential and ensures their effective use. Thus, the goal of the research is to examine theoretical and methodological approaches to the content and structure of the economic potential of a region, to identify the key components in its structure as well as to define the role and areas of interaction between the management component and other components of the economic potential. The workis based on the results of research conducted bythe author in 20122013 years and theoretical provisions in the field of regionalistics. It also uses recent works on the development of economic potential of a region. The work uses both general scientific methods and methodology and traditional research methods such as systemic approach, method of analysis and synthesis, structural and substantive analysis. The article discusses in detail and analyzes the content and structure of the economic potential of a region, identifies its main components and defines the role and areas of interaction between the management component and other components of the economic potential. Suggested areas of interaction between the management component and other components of the economic potential can be useful for local governments and concerned organizations in their activities aimed at modernization of regional structural policy and economic growth priorities.